The race that never slows: Otolaryngology - Head and Neck Surgery residency applicant parameters over time - Schachter, Kaylie; Tritt, Ashley; Young, Meredith; Hier, Jessica; Kay-Rivest, Emily; Le Blanc, Gabriella; Nguyen, Lily HP (Canadian Medical Education Journal, 2023)
Background: There has been an increasing number of Canadian medical graduates who have gone unmatched in the residency selection process. Medical students have been engaging in extracurricular activities outside the formal curriculum which may help to distinguish themselves from their peers in the selection process. To understand how competitiveness in residency selection shapes applicant demographic characteristics and behaviours, this study set out to explore the demographic characteristics and prevalence of reported extra-curricular activities by applicants to Canadian Otolaryngology – Head & Neck Surgery (OTL-HNS) residency across time. Methods: A retrospective, descriptive study reviewed specific sections of the curriculum vitae (CV) of applicants to OTL-HNS programs in Canada. These sections were self-reported, and included research productivity, involvement in volunteer and leadership activities, membership in associations, and honours or awards granted. Data was quantified and analyzed descriptively. Results: Between 2013 to 2017, a total of 267 applicants reported a median of 12.6 research publications, 9.6 volunteer activities, six leadership activities, six association memberships and 9.8 honours/awards. Applicants were younger over time, with proportions of applicants over 30 years old decreasing from 56% in 2013 to 9% in 2017. Conclusion: Applicants to Canadian OTL-HNS residency programs are reporting consistently high numbers of extracurricular activities and were of increasingly younger ages. Medical students are investing significant time and energy to pursue these activities which are above and beyond the formal curriculum, possibly contributing to decreased diversity in applicants for competitive residencies, increasing the likelihood of misrepresentation in residency applications, and likely contributing to medical student burnout.